Analysis of Hard Water Coagulation in Water Sources of Kawatuna using Aloe Vera Plant - Baby Melyta Pallar; Paulus Hengky Abram; Purnama Ningsih (Universitas Tadulako, 2020)
Aloe vera gel is one of the plants that can be used as a natural coagulant. The chemical content in aloe vera has similarities to the cactus with the presence of mucilage or gel which can be used to purify water. This study aimed to determine the ability of aloe vera gel as a natural coagulant for water purification of Kawatuna water source and to determine the optimum volume of aloe vera gel. The steps of the study were preparing water sample, preparing aloe vera gel, coagulating of water, and analyzing parameters of water qualities i.e hardness, turbidity, color, temperature, pH, and total dissolved solids (TDS). The results showed that aloe vera gel was able to be used as a natural coagulant to purify water with the optimum ratio of 1 mL of aloe vera gel in 500 mL of the water sample. Aloe vera gel reduced turbidity, hardness, and color by 58.33, 15.45, and 50.36%, respectively, with a pH of 4.1, temperatures at 30 oC, and TDS of 77.51%. This study concluded that aloe vera gel able to be used as a coagulant to purify water.